2016
DOI: 10.1016/j.kontakt.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between burnout syndrome and empathy among nurses in emergency medical services

Abstract: A B S T R A C TThe aim of the research was to determine the prevalence of burnout syndrome and empathy among general nurses working in standard hospital settings (University Hospital Olomouc), and among general nurses working in emergency medical services, as well as to identify the differences in the degree of burnout syndrome and empathy between the two groups. Another objective was to establish whether there is a relationship between burnout syndrome and empathy in the groups of general nurses specified abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Empathy in the context of healthcare is defined as a cognitive (as opposed to emotional/affective) attribute that involves understanding the experiences and perspective of the patient, combined with the ability to communicate this understanding to the patients (Hojat and Gonnella, 2016). This distinction is very important since it has demonstrated that emotional empathy in nurses is positively correlated with emotional exhaustion (Williams, 1989), and with burnout (Vévodová et al, 2016). On the contrary, empathy as a cognitive attribute of caregivers has a positive role on prevention of burnout and work distress (Hojat, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Empathy in the context of healthcare is defined as a cognitive (as opposed to emotional/affective) attribute that involves understanding the experiences and perspective of the patient, combined with the ability to communicate this understanding to the patients (Hojat and Gonnella, 2016). This distinction is very important since it has demonstrated that emotional empathy in nurses is positively correlated with emotional exhaustion (Williams, 1989), and with burnout (Vévodová et al, 2016). On the contrary, empathy as a cognitive attribute of caregivers has a positive role on prevention of burnout and work distress (Hojat, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Midwives also encounter stress in their profession. Surveys carried out in healthcare facilities showed high levels of stress in health professionals resulting from a lack of time for professional activities, high workload, workplace bullying, management styles and job insecurity (Vévodová et al, 2016). All these may lead to physical and mental health problems (Rodwell, Munro, 2013).…”
Section: Discussionmentioning
confidence: 99%
“… Vévodová et al (2016) also demonstrated a relationship between occupational burnout syndrome and empathy, reporting a weak positive and significant correlation between empathy and emotional exhaustion in general ward nurses working in emergency departments.…”
Section: Differences In the Empathy Scores Of The Three Hospitalsmentioning
confidence: 94%